Placement of reference electrode, electrolyte thickness and three-electrode cell configuration in solid oxide fuel cells: A brief review and update on experimental approach - Jiang, San Ping (The Electrochemical Society, Inc, 2017)
© 2017 The Electrochemical Society. All rights reserved. Cell configuration and placement of reference electrode (RE) have been a subject of intensive interests to the solid oxide fuel cells (SOFCs) communities. Here, the relationship between the position of RE, electrolyte thickness, electrode/electrolyte contact and reliability of 3-electrode cell configuration in electrode polarization and resistance separation is briefly reviewed with particular emphasis on the experimental approach. Numerous modelling studies show that distortion to the electrochemical impedance measurement of electrode reactions on thin electrolyte cells is not avoidable due to the misalignment of working and counter electrodes (WE and CE) and the differences in their electrochemical characteristics. This has been verified experimentally that the asymmetric contact at the electrode/electrolyte interface can cause the shift of equipotential line/surface away from the electrolyte region, leading to the significant distortion in the polarization measurements. However, the distortion effect of misalignment on the equipotential line/surface depends strongly on the electrolyte thickness. In the case of SOFCs with model La 0.8 Sr 0.2 MnO 3 cathode and Ni-yttriastabilized zirconia (Ni-YSZ) cermet anode, the threshold for YSZ electrolyte thickness with equal partitioning of the cell resistance is ∼250 μm. In conclusion, for reliable and accurate polarization and impedance measurements in electrolyte-supported cells, it is suggested that minimum YSZ electrolyte thickness should be 250 μm for plate cells with electrode areas of ∼10 cm 2 and 500 μm for button cells with electrode areas less than 1 cm 2 for symmetric 3-electrode cell configurations with RE positioned on the inactive surface of electrolyte.